Resightings and recoveries of Canada Geese Branta canadensis ringed in West Greenland - Kristiansen, J Nyeland; Fox, A D; Jarrett, N S (Wildfowl, 1999)
Canada Geese Branta canadensis have recently established in West Greenland. Until now their origin and migration routes have been unknown. This paper presents resighting and recovery data of Canada Geese caught during two expeditions to West Greenland: 1997 (10 birds) and 1997 (125 birds). Subsequently, a total of 45 individual birds have been reported. Birds were recovered from northern and central Labrador and New Brunswick, Canada during autumn. During winter the birds were recovered and resighted mainly in Connecticut, New York, and Pennsylvania, USA.